Model Pembelajaran Inklusif Menurut 1 Korintus 12:12-25 dalam Pendidikan Agama Kristen - Tololiu, Naomi; Kondorura, Nessa Tesalonika (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
This article aims to examine and formulate an inclusive model of Christian Religious Education (PAK) at SMP Negeri 1 Parigi, grounded in the theological values of 1 Corinthians 12:12–25. The study uses a qualitative approach, employing the historical-critical hermeneutic method to interpret the biblical text contextually, alongside descriptive field research to explore the actual practices of PAK in the school setting. The findings indicate a gap between the inclusive ideals of the biblical text and the current reality, particularly in the absence of a permanent PAK teacher, low participation among Christian students, and the lack of instructional strategies that accommodate diversity holistically. The article concludes that the body of Christ metaphor can serve as a foundation for building an educational ecosystem that values every student as a dignified member of the learning community. It recommends strengthening the teacher’s role as a mediator of inclusiveness, developing contextual learning strategies based on biblical values, and fostering collaboration between school, church, and family to achieve a liberating and unifying Christian education.